Karakterisasi Anatomi dan Perilaku Kompresi Fundamental Kenaf (Hibiscus cannabinus L.) untuk Potensi Aplikasi Oriented Strand Board (OSB): Anatomical Characterization and Fundamental Compression Behaviour of Kenaf (Hibiscus cannabinus L.) for Potential Oriented Strand Board (OSB) Application - Mohd Nor, Mohd Za’im; Wan Abdul Rahman, Wan Mohd Nazri; Mohamed Tamat, Nur Sakinah; Ohbayashi, Hiroya (PERENNIAL, 2026)
This study evaluates the anatomical characteristics and basic mechanical behaviour of kenaf (Hibiscus cannabinus L.) core with the objective of assessing its suitability as a raw material for oriented strand board (OSB). Anatomical observations (cross, radial and tangential sections) revealed three distinct stem components (bast, core, pith) and showed variation in fibre and vessel element lengths along the stem (top, middle, bottom). Compression testing perpendicular to the grain provided baseline mechanical data relevant to strand production and panel performance. Based on anatomical features and compression response, kenaf core is proposed as a viable alternative biomass feedstock for wood-based composites such as OSB, particularly for short-rotation and urban biomass sources. The work demonstrates promise but highlights the need for further quantitative processing and full-scale panel manufacture/testing (modulus of rupture, modulus of elasticity, internal bond, dimensional stability) to confirm industrial feasibility.